Trialling the preparation for reuse of consumer ICT WEEE in Ireland. (20th May 2020) - Coughlan, Damian; Fitzpatrick, Colin
Abstract: This work investigated the potential of collecting consumer Information & Communication Technology (ICT) Waste Electrical & Electronic Equipment (WEEE) for preparation for reuse in workplaces in Ireland. A series of WEEE to Work and public collection events were held where people were incentivized to return their data-bearing devices (Laptops, Tablets & Smartphones) with free data wiping and destruction being offered on all devices. The collected devices were sent to an approved preparation for reuse organisation where the devices were tested and assessed for their suitability for reuse using both technical and economic criteria. 283 kg of laptops, smartphones and tablets were collected from 10 events of which 60 kg (28%) was suitable for preparation for reuse. A further 308 kg of WEEE outside of the scope of the research was also collected and recycled during the events. Highlights: WEEE to Work events to encourage & promote preparation for reuse. Potential to supplement collection targets with WEEE to Work events. Incentivise returns by offering free data destruction. Increase the return of devices with low collection rates. IT Asset Disposal sector to become preparation for reuse organisations.